A longitudinal study of emotional experience, expressivity, and psychopathology in psychotherapy inpatients and psychologically healthy persons - Leising, Daniel; Grande, Tilman; Faber, Rainer (Journal of clinical psychology, 2010)
The authors investigated changes of emotional experience and expressivity in 34 inpatients undergoing psychodynamic therapy and in 29 healthy persons who were assessed at parallel time intervals. Participants completed 2 measures of psychopathology (Symptom Checklist-90 Revised and Inventory of Interpersonal Problems-64) and took part in relationship episode interviews. The emotional experiences they reported and their nonverbal emotional expressivity during the interviews were assessed by independent raters. Regardless of when they were assessed, the patients reported a greater number of emotions and a greater variety of emotions. Psychopathology in the patient group decreased in the course of treatment, but there were no systematic changes in the emotional domain. The findings challenge the common notion of psychopathology being associated with impaired awareness and expression of emotions.
Gesehen am 13.03.2023